Fun with addition: practise at home - Hurt, Roger; Hurt, Mary Grundy, Lynn N. (Ladybird Books Auburn, 1982)
"Fun with Addition: Practice at Home" is an engaging workbook designed to help young learners develop their addition skills through enjoyable activities. It features a variety of exercises, such as puzzles, games, and colorful illustrations, making math fun and interactive. The book encourages practice in a home setting, reinforcing foundational math concepts while promoting confidence in addition. It$1 (Bs a great resource for parents and educators to support early math learning.s